The Effect of Market Orientation and Entrepreneurial Orientation on the Business Performance of Coffee Shops in Bandung - Fawwaz, Abyan; Brahmana, Sunardi Sembiring (Journal Research of Social Science, Economics, and Management, 2026)
This study examines the influence of Market Orientation (MO) and Entrepreneurial Orientation (EO) on the Business Performance (BP) of coffee shops in Bandung City. The rapid growth of the coffee shop industry has intensified competition, requiring business actors to implement adaptive and competitive strategies. This study employed a cross-sectional survey design using a quantitative approach. Data were collected from 150 coffee shops in Bandung City through a five-point Likert-scale questionnaire distributed via Google Forms, with respondents consisting of owners or managers selected using purposive sampling techniques. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Before testing the structural model, measurement model purification was performed by eliminating indicators with outer loading values below 0.70. The results show that Market Orientation, particularly the MO-2 (Competitor Orientation) dimension, has a positive and significant effect on Business Performance (path coefficient = 0.337; t = 3.531; p = 0.000). In contrast, the effect of Entrepreneurial Orientation on Business Performance was not consistent: the EO-1 and EO-3 dimensions did not demonstrate significant effects, whereas the EO-4 dimension exhibited a negative and significant effect (path coefficient = ?0.352; t = 3.149; p = 0.002). The coefficient of determination (R²) value of 0.121 indicates that Entrepreneurial Orientation and Market Orientation jointly explain 12.1% of the variance in Business Performance. These findings indicate that Market Orientation plays a more consistent and practical role in improving coffee shop performance.